A Community-University Partnership to Improve Access to Fresh Produce among Homebound Seniors - Lauri Wright; Lina Bracht; Lauren M. Vance; Cindy Vann; James B. Epps (University of North Florida, 2017)
Accessing fresh produce is often difficult for homebound seniors, leading to under-consumption and increased risk of chronic disease. Current Meals on Wheels (MOW) programs do not include fresh produce delivery. A MOW agency collaborated with a large non-profit university to design and evaluate the impact of a monthly produce delivery program to homebound seniors. The produce delivery program was systematically designed based on the constructs of the Health Belief Model. Quantitative and qualitative data was collected. The results of the monthly delivery of fresh produce to homebound seniors demonstrated an increased produce intake and increased perceived health value of fruits and vegetables. A processes evaluation was conducted with results used to make immediate improvement in program methods. The university-community partnership strengthened program development and provided expertise for program evaluation. The produce delivery program was an effective way of decreasing barriers to accessing produce and increasing consumption.